Pulmonary veins isolation in a patient with atrial fibrillation and pronounced vagal response: Is it enough? - Dinčić, Dragan; Gudelj, Ognjen; Djurić, Ivica; Marinković, Milan (Vojnosanitetski pregled, 2017)
Introduction. Pulmonary vein isolation (PVI) by antral circumferential ablation is the standard procedure for patients with symptomatic and drug-refractory paroxysmal atrial fibrillation (AF). In some patients addition of ganglionated plexi (GP) modification in anatomic locations to PVI confers significantly better outcomes than PVI alone. Case report. We reported a patient with paroxysmal, symptomatic AF and severe bradycardia a month prior to ablation. The patient was treated with antiarrhythmic drugs without success. Because of severe bradicardia the patient was implanted with a temporary pace maker two days before PVI. During PVI the decision was made to also do a modification of the left GP. Three months after the procedure the patients was in stable sinus rhythm without any symptoms. Conclusion. In selected patients with paroxysmal AF and pronounced vagal response PVI by circumferential antral ablation combined with GP modification during single ablation procedure can produce higher success rates than PVI or GP ablation alone.